The Identity Triangle: toward a unified framework for teacher identity. Issue 3 (27th May 2021) - Dugas, Daryl
ABSTRACT: The Identity Triangle model is proposed as a framework for unifying and advancing research on teacher identity, countering the prevailing approach to teacher education rooted in the language of accountability and competencies. The model is based on a review of the identity literature and elucidated through narratives collected from first-year teachers. Identity is framed around the interactions among a psychological domain, a relational domain, and a behavioral domain. Identity work is framed as seeking coherence among these domains. Benefits of the model are that it draws on growing consensus in the literature that (1) the function of identity is to integrate life experiences into coherence and (2) identity processes are based in narrative. The model also offers resolutions to debates over (1) whether identity is primarily an internal/psychological construct or an external/social performance and (2) whether identity is unitary or contextual. Implications for teacher education research and practice are discussed.